Unlocked Nucleic Acids with a Pyrene‐Modified Uracil: Synthesis, Hybridization Studies, Fluorescent Properties and i‐Motif Stability. Issue 1 (25th November 2013) - Perlíková, Pavla; Karlsen, Kasper K.; Pedersen, Erik B.; Wengel, Jesper
Abstract The synthesis of two new phosphoramidite building blocks for the incorporation of 5‐(pyren‐1‐yl)uracilyl unlocked nucleic acid (UNA) monomers into oligonucleotides has been developed. Monomers containing a pyrene‐modified nucleobase component were found to destabilize an i‐motif structure at pH 5.2, both under molecular crowding and noncrowding conditions. The presence of the pyrene‐modified UNA monomers in DNA strands led to decreases in the thermal stabilities of DNA*/DNA and DNA*/RNA duplexes, but these duplexes' thermal stabilities were better than those of duplexes containing unmodified UNA monomers. Pyrene‐modified UNA monomers incorporated in bulges were able to stabilize DNA*/DNA duplexes due to intercalation of the pyrene moiety into the duplexes. Steady‐state fluorescence emission studies of oligonucleotides containing pyrene‐modified UNA monomers revealed decreases in fluorescence intensities upon hybridization to DNA or RNA. Efficient quenching of fluorescence of pyrene‐modified UNA monomers was observed after formation of i‐motif structures at pH 5.2. The stabilizing/destabilizing effect of pyrene‐modified nucleic acids might be useful for designing antisense oligonucleotides and hybridization probes.